Literature Riview: Determinants of Postpartum Blues - Nancy Olii; Salman Salman; Nurnaningsih Ali Abdul; Siti Choirul Dwi Astuti; Hasnawatty Surya Porouw; Selvi Mohamad; Juli Gladis Claudia; Eka Rati Astuti (Universitas Aisyah Pringsewu, 2023)
Postpartum blues is a kind of psychological problem in the period after childbirth, where a woman feels sad and depressed immediately. Post partum blues symptoms begin to appear two or three days after childbirth and usually go away within a week or two. Objective: to analyze the literature related to the determinants of post partum blues. Methods: articles related to literature review topic were searched in the ScienceDirect, Pudmed. Google Scholar Google Scholar databases and were analyzed using PRISMA through the processes including identification, selection, and finally the assessment of articles according to the inclusion and exclusion criteria. Results: Article searching in chosen databases using keywords in accordance with the study objective resulted in 20 articles which were further selected according to the topics to be reviewed and finally 5 journal articles were discussed in the literature review. The topic to be discussed here was the determinants of postpartum blues. Conclusion: Age, parity, education level, family support, sleep disorders, type of delivery, and readiness to become a mother were involved in the causative factors of Postpartum blues and those factors could be overcome by involving husband, family and the surrounding environment through support for postpartum womenAbstrak: Postpartum blues adalah masalah psikologis pada masa setelah persalinan, dimana seorang perempuan merasakan sedih dan depresi segera. Gejala post partum blues mulai muncul dua atau tiga hari setelah persalinan dan biasanya hilang dalam satu atau dua minggu. Tujuan : untuk menganalisis literatur yang berkaitan determinan post partum blues. Metode: yang digunakan dalam mencari artikel adalah literature review dengan menggunakan database ScienceDirect, Pudmed. google scholar google scholar dan menggunakan PRISMA yakni dengan melalui proses identifikasi, seleksi dan terakhir penilaian artikel sesuai dengan kriteria inklusi dan ekslusi. Hasil: Dari hasil Pencarian Artikel di databased menggunakan keyword atau kata kunci sesuai dengan tujuan penelitian sebanyak 20 artikel, kemudian artikel tersebut di saring sesuai dengan topik yang akan di review sebanyak 5 jurnal dengan judul topik yang dibahas pada literature review yaitu faktor penyebab post partum blues. Kesimpulan: Usia, paritas, tingkat pendidikan, dukungan keluarga, ganguan tidur, jenis persalinan, dan kesiapan menjadi ibu merupakan faktor penyebab terjadinya Postpartum blues dan dapat diatasi dengan melibatkan suami, keluarga dan lingkungan sekitar melalui dukungan pada ibu postpartum